Characterization of p53 p.T253I as a pathogenic mutation underlying Li-Fraumeni Syndrome - Nathaniel C. Holcomb; Amanda M. Harrington; Hong Pu; Berina Halilovic; Nathan R. Shelman; Shulin Zhang; Catherine Sears; Terra Armstrong; Brent Shelton; Lauren Corum; John A. D'Orazio (PLoS ONE, 2025)
We identified a germline TP53 c.758C > T (p.T253I) mutation in the TP53 tumor suppressor gene in a pediatric adrenocortical carcinoma (ACC) patient. Characteristic of pathogenic p53 mutations, we observed upregulation of total p53 protein levels in the patient’s ACC and concurrent suppression of the wild-type (WT) TP53 allele. As ACC can be associated with Li-Fraumeni Syndrome (LFS) and the mutation has not yet been linked to LFS, we sought to characterize the functionality of the T253I mutation. We acquired p53 -/- HEK293 cells and stably transduced them with GFP-tagged wild type (T253) or T253I p53 as well as two established pathogenic p53 mutants (C176Y and R213X). Compared to p53 WT, levels of T253I p53 increased while MDM2 levels decreased, suggesting a loss of MDM2-mediated regulation of T253I p53. Additionally, T253I showed a reduction in DNA damage responsive events, diminished DNA binding capabilities, and blunted transactivation capacity. These experimental data lead us to conclude that T253I represents a pathologic variant in TP53 that may predispose to LFS-associated tumors.